Investigating Conventionalised Impoliteness Strategies Used by Main Characters in Instant Family - Qaniah, Binti (SPHOTA: Jurnal Linguistik dan Sastra, 2025)
Comedy movies frequently present impolite utterances due to the emotional dynamics that color character interactions. This study aimed to identify and examine the types of conventionalised impoliteness strategies used by the main characters in the movie “Instant Family”. It adopted Culpeper’s (2011) theory of conventionalised impoliteness, which classifies nine commonly recognised types of offensive utterances. Using a descriptive qualitative method, the data were collected from the movie script and were analysed through categorisation and contextual interpretation. The findings revealed that all nine types of strategies appeared in the characters’ utterances, with pointed criticisms/complaints and insults being the most frequent. These results suggested that impoliteness strategies were influenced by the characters’ emotional roles and power dynamics within the family context. In sum, this study contributed to a better understanding of how conventionalised impoliteness functioned in fictional family discourse and expanded the application of interactional pragmatics in media-based studies.